Can Relational Egalitarians Supply Both an Account of Justice and an Account of the Value of Democracy or Must They Choose Which? - Andreas Bengtson; Kasper Lippert-Rasmussen (Ergo, An Open Access Journal of Philosophy)
Construed as a theory of justice, relational egalitarianism says that justice requires that people relate as equals. Construed as a theory of what makes democracy valuable, it says that democracy is a necessary, or constituent, part of the value of relating as equals. Typically, relational egalitarians want their theory to provide both an account of what justice requires and an account of what makes democracy valuable. We argue that relational egalitarians with this dual ambition face the justice-democracy dilemma: Understanding social relations in such a way that renders relational egalitarianism plausible as an answer to what makes democracy valuable comes at the price of understanding social relations in a way that makes it less plausible as a theory of justice, and vice versa. We also argue that there is no easy way out of the dilemma and that relational egalitarians, who want relational equality to provide both accounts mentioned, may simply have to set their ambitions lower on behalf of relational equality.